PH‐Responsive and Recyclable Hydrogels for Gas Releasing and Scavenging. Issue 8 (27th February 2023) - Zhou, Xiaozhuang; Kandalai, Shruthi; Hossain, Farzana; Zhang, Nan; Li, Huapeng; Zheng, Qingfei
Abstract: Gas‐releasing/scavenging hydrogels have wide applications in biomedical and industrial fields. However, the covalently crosslinked nature of these existing materials makes them difficult to degrade or recycle, leading to a waste of raw materials and aggravating environmental pollution. Herein, a new class of pH‐responsive and recyclable hydrogels with versatile gas‐releasing and scavenging properties is reported, utilizing pH changes to reversibly control disassembly and reassembly of the hydrogel network. The initial hydrogels are constructed via the one‐pot radical polymerization and contain dynamic molecular networks based on hydrophobic interactions, which can disassemble when the materials are placed in low pH solutions. The disassembled copolymer chains can reform hydrogels, following supplementation with fresh mineral salts and micelle monomers in neutral solutions. Moreover, the mineral salts used to reform hydrogels can function as gas donors or scavengers, endowing these hydrogels with versatile gas‐releasing and consuming properties. Overall, this research provides a facile and environmentally friendly method to recycle hydrogels with gas‐releasing and gas‐scavenging properties, which have potential applications in diverse fields, including wound healing, wastewater management, and gas therapy for diseases. Abstract : A novel copolymer recycling strategy is reported in this study allowing for the construction of sodium dodecyl sulfate (SDS) micellar hydrogels containing diverse types of mineral salts for pH‐controlled gas releasing and scavenging.